Snapshots of Dynamic Adaptation: Two‐Dimensional Molecular Architectonics with Linear Bis‐Hydroxamic Acid Modules. (27th November 2019) - Jing, Chao; Zhang, Bodong; Synkule, Sabine; Ebrahimi, Maryam; Riss, Alexander; Auwärter, Willi; Jiang, Li; Médard, Guillaume; Reichert, Joachim; Barth, Johannes V.; Papageorgiou, Anthoula C.
Abstract: Linear modules equipped with two terminal hydroxamic acid groups act as the building block of diverse two‐dimensional supramolecular motifs and patterns with room‐temperature stability on the close‐packed single‐crystal surfaces of silver and gold, revealing a complex self‐assembly scenario. By combining multiple investigation techniques (scanning tunneling microscopy, atomic force microscopy, X‐ray photoelectron spectroscopy, and density functional theory calculations), we analyze the characteristics of the ordered assemblies which range from close‐packed structures to polyporous networks featuring an exceptionally extended primitive unit cell with a side length exceeding 7 nm. The polyporous network shows potential for hosting and promoting the formation of chiral supramolecules, whereas a transition from 1D chiral randomness to an ordered racemate is discovered in a different porous phase. We correlate the observed structural changes to the adaptivity of the building block and surface‐induced changes in the chemical state of the hydroxamic acid functional group. Abstract : Mosaikarbeit : Die komplexe Entwicklung von Strukturen als Funktion des chemischen Zustands wird mittels Rastersondenmikroskopie und Röntgen‐Photoelektronenspektroskopie visualisiert. Mit zunehmender Deprotonierung eines Adsorbats auf Ag(111) entstehen komplexe Netzwerke mit chiralen Poren. Ihre Funktionalität wird anhand eines polyporösen Netzwerks veranschaulicht, in dem sich chirale supramolekulare Gastmoleküle enantioselektiv bilden.